No Difference in Myosin Kinetics and Spatial Distribution of the Lever Arm in the Left and Right Ventricles of Human Hearts - Duggal, Divya; Requena, S.; Nagwekar, Janhavi; Raut, Sangram; Rich, Ryan; Das, Hriday; Patel, Vipul; Gryczynski, Ignacy; Fudala, Rafal; Gryczynski, Zygmunt; Blair, Cheavar; Campbell, Kenneth S.; et al. (Frontiers in Physiology, 2017)
The systemic circulation offers larger resistance to the blood flow than the pulmonary system. Consequently, the left ventricle (LV) must pump blood with more force than the right ventricle (RV). The question arises whether the stronger pumping action of the LV is due to a more efficient action of left ventricular myosin, or whether it is due to the morphological differences between ventricles. Such a question cannot be answered by studying the entire ventricles because any observed differences would be wiped out by averaging the information obtained from trillions of myosin molecules present in a ventricle. We therefore searched for the differences between single myosin molecules of the LV and RV of failing hearts in-situ. We show that the parameters that define the mechanical characteristics of working myosin (kinetic rates and the distribution of spatial orientation of myosin lever arm) were the same in both ventricles. These results suggest that there is no difference in the way myosin interacts with thin filaments in ventricles of failing hearts, and that the difference in pumping efficiencies are exclusively morphological.